IMPLEMENTASI DATA MINING UNTUK MENENTUKAN POLA PENJUALAN DI RAHAYU MART MENGGUNAKAN ALGORITMA APRIORI - Bina Cahya Pamungkas, ihya16092002; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
The Apriori algorithm is a method used to discover patterns among a set of items. By analyzing all recorded sales transactions, it helps in determining and developing more accurate and targeted promotions. Rahayu Mart faces a challenge in understanding what customers want and need, as well as how they shop. Identifying frequently purchased items by customers can assist in making appropriate business decisions and serve as a consideration for sales strategies. By applying the Apriori algorithm, consumer purchasing patterns and the influence between items can be uncovered, enabling more effective business insights.